2000
DOI: 10.1046/j.1464-410x.2000.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term outcome after laparoscopic nephroureterectomy: a comparison with open nephroureterectomy

Abstract: 12%). Of the TCCs in this group half were G3 and half were invasive (pT1±3). In the ONU group there were more ureteric tumours because of selection criteria and overall 16 (39%) were G3 and half were invasive. Information on nodal status was available in one LNU and two of the ONU reports. Within a mean follow-up of 32.9 months for LNU and 42.3 months for ONU, nine (21%) of the ONU group and four (16%) of the LNU group had died, with a mean survival of 15.1 and 17 months, respectively, after surgery (not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 21 publications
(35 reference statements)
2
52
0
1
Order By: Relevance
“…However, several investigators have recently introduced laparoscopic procedures to radical nephroureterectomy and suggested their benefit for patient recovery with disease control comparable to that of traditional open surgery [4][5][6]. Minor complications after LNU have been reported in 7-40% of patients and major complications in 4.8-8% [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several investigators have recently introduced laparoscopic procedures to radical nephroureterectomy and suggested their benefit for patient recovery with disease control comparable to that of traditional open surgery [4][5][6]. Minor complications after LNU have been reported in 7-40% of patients and major complications in 4.8-8% [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…McNeill et al reported favorable longterm outcomes after laparoscopic nephroureterectomy compared with open nephroureterectomy; however, information on nodal status was available in only 4% of cases [6]. Although the therapeutic effectiveness of lymphoadenectomy for upper urinary tract transitional cell carcinoma has been controversial, extensive lymphoadenectomy is presently recommended in high-grade or high-stage tumors, because microscopic lymph node metastasis may be cured by surgery alone or with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 However, the procedure is technically difficult and is associated with a steep learning curve. We feel that the handassisted approach offers several advantages over the pure laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Since Clayman et al reported in 1991 the initial case of laparoscopic nephroureterectomy (LNU), there have been reports demonstrating that LNU decreases pain and accelerates convalescence of patients (Jarrett et al, 2001). It can be done either with pure laparoscopic approach or with the help of a hand-assisted device (McNeill et al, 2000;Gill et al, 2000;Shalhav et al, 2000;Chen et al, 2001). Operative technique of a hand-assisted nephroureterectomy (HALNU; Chen et al, 2001): The patient is placed in a 60º oblique position with no change in posture during the entire procedure.…”
Section: Laparoscopic Nephroureterectomy and Bladder Cuff Eecision Fomentioning
confidence: 99%
“…Traditionally, open simultaneous bilateral nephroureterectomy is usually done via a long midline incision extending from the xyphoid to the symphysis pubis. To perform unilateral LNU smoothly, the patient has to be positioned at 60º oblique to a full lateral flank position for better exposure and easier dissection because the surrounding organs are displaced downward by gravity (Jarrett et al, 2001;McNeill et al, 2000;Gill et al, 2000;Shalhav et al, 2000). For laparoscopic bilateral nephroureterectomy (LBNU) to be completed in one session with the above-mentioned approach, one needs to do additional position changes to perform the nephroureterectomy on the contralateral side.…”
Section: Simultaneous Laparoscopic Bilateral Nephroureterectomy (Nephmentioning
confidence: 99%